2018
DOI: 10.1021/acs.joc.8b00349
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Properties of Aromatic Oligoamides Bearing Pyrrole Rings

Abstract: N-Alkylbenzanilides generally exist in cis conformation both in the crystalline state and in various solvents, and this cis conformational preference can be utilized to construct dynamic helical oligoamides. Here, we synthesized the pyrrole-containing amides 2-5 and their oligomers 6-8 and examined their conformations in the crystalline state and in solution. All the N-methylated amides showed cis conformational preference in solution, but the ratio of the cis isomer was decreased when the amide bond was attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…[54] Similarly to Nmethyl benzanilide, N-methyl-N-phenyl pyrrole 2-carboxamide exhibits predominantly the cis conformation but the proportion of cis conformer decreases in N-methyl-N-(4pyrrole) benzamide as demonstrated by 1 H NMR at low temperature in CD 2 Cl 2 . [20] A cis to trans switching effect induced by an environmental change (solvent or pH) was demonstrated by Okamoto and co-workers for N-methyl aromatic amides containing 2,6-disubstituted pyridine (Figure 6). [17] The protonation of the pyridyl ring under acidic conditions leads to a pyridinium core which is able to stabilize the trans conformation through the establishment of hydrogen-bonding with the oxygen of the adjacent carbonyl group.…”
Section: Local Conformational Preferences Of Nn-disubstituted Amidesmentioning
confidence: 89%
See 3 more Smart Citations
“…[54] Similarly to Nmethyl benzanilide, N-methyl-N-phenyl pyrrole 2-carboxamide exhibits predominantly the cis conformation but the proportion of cis conformer decreases in N-methyl-N-(4pyrrole) benzamide as demonstrated by 1 H NMR at low temperature in CD 2 Cl 2 . [20] A cis to trans switching effect induced by an environmental change (solvent or pH) was demonstrated by Okamoto and co-workers for N-methyl aromatic amides containing 2,6-disubstituted pyridine (Figure 6). [17] The protonation of the pyridyl ring under acidic conditions leads to a pyridinium core which is able to stabilize the trans conformation through the establishment of hydrogen-bonding with the oxygen of the adjacent carbonyl group.…”
Section: Local Conformational Preferences Of Nn-disubstituted Amidesmentioning
confidence: 89%
“…[19] Tanatani and co-workers have recently explored the conformational preferences of the N-alkylated amide bonds on the pyrrole group in heterooligomers containing both pyrrole and arene rings. [20] More related to N-alkylated benzamides, oligomeric Nsubstituted aminomethyl benzamides, or arylopeptoids, possess a backbone-methylene group adjacent to the phenyl ring. In connection with their pioneering work on peptoids, [14] Zuckermann and co-workers briefly mentioned the synthesis of such oligomers in few patents back in the 1990's, [21] but arylopeptoids were further developed by other groups taking advantages of the great chemical diversity available by variation of the substituents on the nitrogen.…”
Section: Classes Of N-alkylated Aromatic Oligoamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tojo et al synthesized the pyrrole-containing amides and their oligomers, and investigated their conformations in solution and in the crystalline state. [92] Compared with known foldamers with cis-amide conformation, oligoamides bearing a pyrrole ring displayed different dynamic folding properties. Urushibara et al reported the synthesis of alternately N-alkylated aromatic amide oligomers.…”
Section: Helical Polyamidesmentioning
confidence: 99%